Recuperação de informações em livros e monografias: algoritmo conceitual e prático para maior revocação - Lamas, Francisca Maria de Mello Leal Santiago (1992)
Improvement of subject access to books and monographies, through more exaustive indexing processes, without substantially decreasing information retrieval precision. The applied methodology used titles, subtitles and tables of contents of books and monographies to identify words with a strong capability of conceptual representation for additional subject headings or indexing terms formulation. The research consisted of the analysis of books and monographies included in the bibliographical collection of two different Brazilian Information Systems: a coordinated system and a pre-coordinated one, respectively, the library of the Banco Nacional de Desenvolvimento Econômico e Social -BNDES, and the BIBLIODATA (CALCO) Network. From the titles, subtitles and tables of contents of these documents, words, expressions and proper names were selected for the construction of appropriate subject headings. Hierarchical levels were established to documents' tables of contents, according to their structures. Research results have led to substantial increases in subject access when (compared to subject cataloguing made by the two above-mentioned Information Systems. Results demonstrated the potential of titles, subtitles and tables of contents for identifying words with a high degree of documents' conceptual representation. The results have also demonstrated that the use of words extracted from titles, subtitles and until the second hierarchical level of tables of contents of books and monographies with a less specific approach of subjects, and down to the third hierarchical level of those documents with a more specific approach, the subject headings or indexing terms formulation achieves exaustive and consistent levels, with a great and pertinent conceptual representativeness for future information retrieval. Additionally, the research has pointed out deficiencies in the indexing languages used by both examined In·format i on Systems, and has confirmed the 1imitations of subject access to books and monographies dued to the reduced number of subject headings assigned by these Systems. A careful analysis of both indexing languages and indexing policies used by the two Information Systems is suggested to improve the quality of their services.